Factors Influencing Access to Cochlear Implantation in Deaf and Hard-of-Hearing Children in Southern California. Issue 2 (February 2019) - Moshtaghi, Omid; Kuan, Edward C.; Mahboubi, Hossein; Khoshab, Nima; Zardouz, Shawn; Yau, Amy Yuk-Yee; Rothholtz, Vanessa S.; Lin, Harrison W.; Djalilian, Hamid R.
Abstract : Objective: To determine the epidemiologic relationship of family demographics and educational resources with parental knowledge of and willingness for their children to receive cochlear implantation (CI) for deaf and hard-of-hearing (DHH) children. Methods: A total of 213 parents of DHH children were surveyed at local schools, specialized camps, and clinics in Southern California. Data on parents were solicited, including income, insurance status, education level, hearing status, primary language, and motivations towards CI. Results: Sixty-six surveys were included in the analysis. Three of these patients had already undergone CI, thus of the 63 children without CI, 59% had been presented with the option of CI by a healthcare professional and 27% were willing to have their child undergo CI. Willingness for children to undergo CI was statistically higher in families with an annual income less than 15, 000 or more than 75, 000 ( p = 0.02), and children enrolled in specialized schools for DHH ( p = 0.02). The leading reasons for unwillingness to undergo CI were risks of surgery (17%) and discouragement from others (14%). Conclusion: A significant gap exists between the number of CI candidates and families and willingness to undergo CI. The difference could be related to socioeconomic status and the patient's school type. This underscores the importance of parental education through the use of a multi-disciplinary team to ensure all hearing rehabilitation options are explained. Abstract : Supplemental Digital Content is available in the text